Gas Discharge Plasmas and Their Applications (GDP 2019) 14th International Conference, September 15-21, 2019, Tomsk, Russia abstracts - Korolev electrophysicist Professor of Tomsk Polytechnic University, Doctor of physical and mathematical sciences; Koval specialist in the field of electronics Professor of Tomsk Polytechnic University, Doctor of technical sciences (TPU Publishing House, 2019)
The book contains abstarcts of oral and poster reports presented at the 14th International Conference "Gas Discharge Plasmas and Their Applications" (GDP 2019). This event is a continuation of conferences on gas discharge physics held in Russia since 1984, as well as seminars and conferences on the technological application of low-temperature plasma. The conference is held every 2 years in different cities of the Russian Federation. This year, the wonderful Siberian city of Tomsk, known for its intellectual environment, was chosen as the venue. The program of the Conference covers a wide range of technical areas and modern aspects of the physical processes occurring in generators of lowtemperature plasma, low and high-pressure discharges, pulsed plasma sources, surface modification, and other gas-discharge technologies.